API analytics for product managers : understand key API metrics that can help you grow your business - Goyal, Deepa (Packt Publishing, 2023)
Research, strategize, market, and continuously measure the effectiveness of APIs to meet your SaaS business goals with this practical audiobook About This Audiobook Transform your APIs into revenue-generating entities by turning them into products Meet your business needs by improving the way you research, strategize, market, and measure results Create and implement a variety of metrics to promote growth In Detail APIs are crucial in the modern market as they allow faster innovation. But have you ever considered your APIs as products for revenue generation? API Analytics for Product Managers takes you through the benefits of efficient researching, strategizing, marketing, and continuously measuring the effectiveness of your APIs to help grow both B2B and B2C SaaS companies. Once you've been introduced to the concept of an API as a product, this fast-paced guide will show you how to establish metrics for activation, retention, engagement, and usage of your API products, as well as metrics to measure the reach and effectiveness of documentation--an often-overlooked aspect of development. Of course, it's not all about the product--as any good product manager knows; you need to understand your customers' needs, expectations, and satisfaction too. Once you've gathered your data, you'll need to be able to derive actionable insights from it. This is where the audiobook covers the advanced concepts of leading and lagging metrics, removing bias from the metric-setting process, and bringing metrics together to establish long- and short-term goals. By the end of this audiobook, you'll be perfectly placed to apply product management methodologies to the building and scaling of revenue-generating APIs. Audience If you're a product manager, engineer, or product executive charged with making the most of APIs for your SaaS business, then this audiobook is for you. Basic knowledge of how APIs work and what they do is essential before you get started with this audiobook, since it covers the analytical side of measuring their performance to help your business grow.